Becoming men : Black masculinities in a South African township - Langa, Malose (Wits University Press, 2020)
Becoming Men is the story of 32 boys from Alexandra, one of Johannesburg's largest townships, over a period of twelve seminal years in which they negotiate manhood and masculinity. Psychologist and academic, Malose Langa documents what it means to be a young black man in contemporary South Africa.